2019
DOI: 10.1021/acs.energyfuels.8b04179
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Functionalized Biocarbon for Mercury Capture

Abstract: In this study, functionalized biocarbon (FBC) as a sorbent to capture mercury (Hg) from flue gas was developed and tested. The sorbent before and after Hg capture was characterized. The developed sorbent was tested for elemental Hg (Hg0) capture efficiency in a (i) Hg pulse injection test, in an argon atmosphere, (ii) simulated flue gas of (a) 350 ppm of SO2, 5% O2, and balanced with N2 or (b) 300 ppm of NO2, 5% O2, and balanced with N2, and (iii) coupon test in a commercially operating coal-fired power plant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…To date, activated carbon injection technology is considered as a promising mercury control technology for coal-fired power plants with the advantage of guaranteed high performance in vapor phase mercury removal and many attempts have been made to make it more commercial acceptable by lowering down the operating cost in recent years, including sorbent modification with halogen and sulfur , to improve the mercury uptake capacity of sorbents or replacing costly commercial activated carbon with other low-cost sorbents prepared from waste materials, such as biomass and petroleum coke . Emphasis is also given to prepare the surface-modified adsorbents using different procedures, such as solution impregnation, , heat treatment, , plasma treatment, , and microwave treatment, to enhance the potential for mercury adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…To date, activated carbon injection technology is considered as a promising mercury control technology for coal-fired power plants with the advantage of guaranteed high performance in vapor phase mercury removal and many attempts have been made to make it more commercial acceptable by lowering down the operating cost in recent years, including sorbent modification with halogen and sulfur , to improve the mercury uptake capacity of sorbents or replacing costly commercial activated carbon with other low-cost sorbents prepared from waste materials, such as biomass and petroleum coke . Emphasis is also given to prepare the surface-modified adsorbents using different procedures, such as solution impregnation, , heat treatment, , plasma treatment, , and microwave treatment, to enhance the potential for mercury adsorption.…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 30 Biomass char is an ideal adsorbent for mercury removal due to its low price, abundant surface functional groups, simple raw materials, and environmental protection. 31 , 32 …”
Section: Introductionmentioning
confidence: 99%
“…29,30 Biomass char is an ideal adsorbent for mercury removal due to its low price, abundant surface functional groups, simple raw materials, and environmental protection. 31,32 The parameters in the experiment will also have a great impact on the experimental results. Zhao et al 33 showed that the change of Hg 0 removal efficiency with the increase of reaction temperature is non-monotonical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation